Understanding the science of Gandhi's experiments with the truth - Kok, Jia Ming (Nanyang Technological University, 2022)
Gandhi is perhaps most widely known as the purveyor of non-violent resistance in India’s struggle for independence, and from one his important works, Hind Swaraj, it can also be surmised that Gandhi was opposed to modern civilisation through the advancement of science and technology. This paper wishes to elucidate the fact that the assumption about Gandhi was not true, and that he was in fact quite the scientist himself. Through an analysis of Gandhi’s thoughts and experiments as well as the circumstances surrounding India at the time, this paper argues that even though Gandhi was not against science, the influential figures in India’s scientific and political landscape painted a very different picture of him and ignored his thoughts on science. This resulted in the dissociation of Gandhi with the scientific community despite his involvements and findings in the fields of dietetics and medicine.